A Rare Presentation of Severe Preeclampsia with Acute Pancreatitis - Raguraman, S.; Muhunthan, K.; Giridaran, S.; Guruparan, K.; Musamil Ismail, M. (Journal of South Asian Federation of Obstetrics and Gynaecology, 2022)
Aim: The aim of the article is to illustrate that women with preeclamptic organ dysfunction can present with a clinical picture of acute pancreatitis. Background: Pancreatitis is a rare condition complicating pregnancy with a quoted incidence of 1–3 cases per 10,000 deliveries, with maternal mortality and fetal loss closer to 3%. Currently, there is increasing speculation that in the absence of any known risk factors, pancreatitis may be associated with a rare spectrum of preeclampsia. Case description: A 25-years-old primigravida at a period of gestation of 34 weeks presented with an acute onset of epigastric pain/tenderness and vomiting of one-day duration. Her BMI was 18 kg/m2 and she did not have any risk factors for acute pancreatitis. Other known etiologies of acute pancreatitis were excluded, but an ultrasound scan revealed swollen pancreas with a thin rim of free fluid in the splenorenal pouch with normal gallbladders. Also, serum amylase was significantly elevated. On the 3rd day of her illness, blood pressure was persistently elevated along with albuminuria and with a falling trend of platelet count. Further, she developed acute renal failure with metabolic acidosis. A category 2 cesarean section was performed, and a healthy baby was delivered. On the 4th postoperative day, her biochemical parameters were back to normal. A contrast-enhanced computed tomography of the abdomen performed on the 4th postoperative day showed features suggestive of resolving interstitial pancreatitis. Conclusion: In conclusion, acute pancreatitis should be considered as a complication of preeclampsia, especially in patients deteriorating despite management of preeclampsia.
Keywords: CT abdomen; Pancreatitis; Preeclampsia.